(untitled) (Eurasian Journal of Ecology, 2016)
This article defined the current state of rangeland vegetation Kyzylaryk rural district, compiled a list of plant species identified supply of forage plants. The studies following recommendations were made: correct use of natural pastures, measures lsobe plant resources.